Market Anomaly Testing: Phenomena of Day of the Week Effect and Month of the Year Effect on IDX80 in Indonesia Stock Exchange - Fransiska Shasa Yolanda; Maria Theresia Ernawati; Caecilia Wahyu Estining Rahayu (Journal of Management and Business Environment (JMBE), 2022)
This study aims at determining occurrence of day of the week effect, Monday effect, weekend effect, month of the year effect, and January effect on IDX80 stock trading in the Indonesia Stock Exchange. This is an empirical study on trading time (daily and monthly) and stock returns using comparative method. The population is companies incorporated in the IDX80 index on the Indonesia Stock Exchange. Applying purposive sampling method, the sample was 70 companies consistently listed in the IDX80 index and were actively trading. The data covering daily and monthly stock returns for the period 1 February 2019 - 31 January 2020 were analyzed using Kruskal Wallis and Mann Whitney U Test/Wilcoxon Sum Rank Test. The results show that during the study period, market anomalies occurred in the Indonesian Capital Market were the day of the week effect, Monday effect, and month of the year effect. While market anomalies that haven’t been proven to occur in the Indonesian Capital Market were the weekend effect and the January effect.